Method for treating spent denitration catalyst and fly ash
Through the crushing and magnetic separation of waste denitrification catalysts, combined with thermal alkali and pickling technology, the coordinated treatment of waste liquid and fly ash is achieved efficiently recycling of titanium, tungsten, vanadium and other resources and silicon products in waste denitrification catalysts. , solves the problems of low resource recovery rate and excessive waste liquid and waste residue, and reduces environmental protection costs.
Patent Information
- Application Number
- CN202111093709.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-17
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-09-17
AI Technical Summary
In the prior art, the resource recovery rate and excessive waste liquid waste residue during the recycling process of waste denitrification catalysts lead to high environmental protection costs and waste resources.
By pretreating the waste denitrification catalyst and grinding to a particle size D90 below 800 nm, combining magnetic separation of iron, followed by thermal alkali reaction and pickling treatment, and multiple solid-liquid separations are performed using waste acid and waste alkali liquid and fly ash. and extraction to achieve efficient recycling of titanium, tungsten, vanadium and other resources and extraction of silicon products.
The silicon extraction rate of more than 90% and the silicon product purity of more than 94% has been achieved, the waste liquid and waste residue in the recycling process of waste denitrification catalyst is reduced, environmental protection costs are reduced, and the purpose of waste control is achieved.
Smart Images

Figure CN115815283B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of solid waste disposal, and in particular to a method for treating waste denitration catalyst and fly ash. Background Art
[0002] The core of the flue gas denitration device of a thermal power plant is the denitration catalyst, and the life of the denitration catalyst is generally about 3 years. Therefore, a large amount of waste catalysts are generated every year. If they are not properly handled, it will not only cause huge waste, but also seriously pollute the environment. The main components of waste denitration catalysts are titanium dioxide, tungsten trioxide, vanadium pentoxide, etc. Resource utilization is the most ideal way to dispose of waste denitration catalysts. For waste denitration catalysts whose intrinsic catalytic activity has not been significantly reduced, the catalytic activity of the catalyst can be restored to 90-100% of the initial activity through regeneration. Therefore, for waste denitration catalysts with intact structures, physical and chemical methods can be used to regenerate and restore the activity of the catalyst. For damaged waste denitration catalysts, they must be treated by recycling and reuse methods to extract metal resources such as vanadium, tungsten, titanium and molybdenum, turning waste into treasure and harm into benefit. Catalyst regeneration and recovery technology is an effective way to restore catalyst activity, extend service life, reduce operating costs, and reduce waste treatment.
[0003] Traditional waste denitrification catalyst recovery technologies mainly include sodium or calcium roasting-water leaching, wet acid leaching, alkali leaching, etc. Beijing Low Carbon Clean Energy Research Institute has developed a waste denitrification catalyst recovery process package with simple process and high maturity, which can achieve the complete recovery of TiO2, V2O5 and WO3 in waste denitrification catalyst. However, no matter which type of catalyst recovery wet process is used, it will produce too much waste liquid and waste residue, consuming a lot of environmental protection costs, which is a major obstacle to the commercial promotion of the recovery process.
[0004] CN110548748A discloses a method for the coordinated melting treatment of waste SCR flue gas denitration catalyst and fly ash, wherein the waste catalyst powder obtained by pre-treatment methods such as crushing, drying, and screening the waste SCR flue gas denitration catalyst is uniformly mixed with fly ash in a certain proportion, and after adding additives, it is subjected to high-temperature melting treatment and rapid cooling operation to obtain a glassy slag with low environmental hazards. Although this method can achieve "waste treatment with waste, coordinated disposal" and achieve harmless treatment of hazardous solid waste, the treatment process consumes a lot of energy because it adopts a high-temperature melting process (1200-1500°C) for roasting for more than 60 minutes. In addition, this method only treats the heavy metals in the waste SCR catalyst and fly ash harmlessly, but resources such as TiO2, V2O5, WO3 and SiO2 have not been effectively recycled, resulting in a waste of high value-added resources.
[0005] CN104261415A discloses a method for completely recovering silicon dioxide from waste SCR catalysts. In this method, the crushed waste SCR catalysts are soaked in water to remove impurities. After impurities are removed, the powder is subjected to a hot alkali reaction with an excess of 60-80wt% concentrated alkali solution. The pH of the filtrate after the reaction is adjusted in stages by adding sulfuric acid to obtain a silicic acid filter cake. Finally, the silicic acid filter cake is purified and washed with water in a mixed acid of dilute sulfuric acid and oxalic acid at 40-60°C. Although high-purity silicon dioxide can be obtained, this method uses a large amount of high-concentration alkali solution and multiple types of acids, generates excessive waste liquid, and aggravates environmental pollution. In addition, this method does not disclose the disposal problem of Na2TiO3 after the hot alkali reaction.
[0006] CN108285163A discloses a preparation method and application of desiliconized fly ash. The method can produce desiliconized fly ash with an aluminum-silicon ratio of 3.2-3.8 by crushing, calcining, medium-temperature acid treatment, alkali washing and water washing of coal gangue. Although the preparation process is simple and easy to operate, the amount of acid and alkali used is relatively high, resulting in excessive acid and alkali waste liquid. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems of low resource recovery rate and excessive amount of waste liquid and waste residue in the waste denitration catalyst recovery process in the prior art, and to provide a method for treating waste denitration catalyst and fly ash.
[0008] In order to achieve the above object, the first aspect of the present invention provides a method for treating spent denitration catalyst and fly ash, the method comprising the following steps:
[0009] (1) Pre-treating the spent denitration catalyst, and then grinding, crushing, and screening to obtain a crushed material, wherein the particle size D90 of the crushed material is less than 800 nm;
[0010] (2) mixing the crushed material with an alkaline solution to perform a first thermal alkali reaction, and then performing solid-liquid separation to obtain a first high-titanium slag and a waste alkali solution;
[0011] (3) removing iron from the first high-titanium slag to obtain a second high-titanium slag;
[0012] (4) pickling the second high-titanium slag and then performing solid-liquid separation to obtain titanium-tungsten powder and waste acid liquid;
[0013] (5) mixing the waste alkali liquid with fly ash to carry out a second hot alkali reaction, and then performing solid-liquid separation to obtain desiliconized fly ash and liquid phase A;
[0014] (6) using waste acid to adjust the pH value of liquid phase A to 8.5-10 for precipitation reaction, and then performing solid-liquid separation to obtain silicon-containing precipitate and liquid phase B;
[0015] (7) washing the silicon-containing precipitate and then roasting it to obtain a silicon product;
[0016] (8) Extracting the liquid phase B to obtain an extract; and then back-extracting the extract to obtain a vanadium-tungsten solution.
[0017] Through the above technical solution, the present invention has the following advantages:
[0018] (1) The method of the present invention can achieve a silicon extraction rate of more than 90% and a silicon product purity of more than 94% at normal temperature and pressure, which can meet the raw material requirements of the foundry industry above level IV. At the same time, it can also effectively recycle resources such as vanadium, tungsten, and titanium in the waste denitrification catalyst. Under alkaline conditions, the extraction of vanadium and tungsten can achieve an extraction efficiency of more than 98%;
[0019] (2) In the process of recovering the waste denitration catalyst, the method of the present invention can effectively reduce the contents of Al2O3, SiO2 and Fe2O3 in the titanium tungsten powder by crushing the waste denitration catalyst to a particle size D90 of less than 800 nm and combining it with a magnetic separation iron removal process; by using the waste acid and waste alkali generated in the process of recovering the waste denitration catalyst to treat the fly ash associated with the waste denitration catalyst, combined with the waste denitration catalyst recovery process, not only can a silicon extraction rate of more than 90% and a silicon product purity of more than 94% be achieved, but also the aluminum-silicon ratio of the desiliconized fly ash can be improved;
[0020] (3) The method of the present invention utilizes the waste acid and waste alkali generated in the process of recovering the waste denitrification catalyst to treat the fly ash associated with the waste denitrification catalyst. While reducing the waste liquid, the fly ash can also be reduced. On the basis of ensuring the quality of high value-added product recovery, the amount of waste liquid and waste residue in the process of recovering the waste denitrification catalyst is reduced, and the environmental protection cost of recovering the waste denitrification catalyst is reduced, thereby achieving the purpose of treating waste with waste, which is beneficial to reducing costs and protecting the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is the XRD spectra of fly ash, desiliconized fly ash of Example 1 and desiliconized fly ash of Comparative Example 2. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] In the present invention, unless explicitly stated, "first", "second" and "third" do not represent the order of precedence, nor do they limit the materials or operations. They are only used to distinguish the materials or operations. For example, the "first" and "second" in the "first high-titanium slag" and the "second high-titanium slag" are only used to distinguish to indicate that they are not the same fly ash; the "first", "second" and "third" in the "first solid phase", "second solid phase" and "third solid phase" are only used to distinguish to indicate that they are not the same solid phase. The other terms are similar and will not be repeated here.
[0024] A first aspect of the present invention provides a method for treating spent denitration catalyst and fly ash, the method comprising the following steps:
[0025] (1) Pre-treating the spent denitration catalyst, and then grinding, crushing, and screening to obtain a crushed material, wherein the particle size D90 of the crushed material is less than 800 nm;
[0026] (2) mixing the crushed material with an alkaline solution to perform a first thermal alkali reaction, and then performing solid-liquid separation to obtain a first high-titanium slag and a waste alkali solution;
[0027] (3) removing iron from the first high-titanium slag to obtain a second high-titanium slag;
[0028] (4) pickling the second high-titanium slag and then performing solid-liquid separation to obtain titanium-tungsten powder and waste acid liquid;
[0029] (5) mixing the waste alkali liquid with fly ash to carry out a second hot alkali reaction, and then performing solid-liquid separation to obtain desiliconized fly ash and liquid phase A;
[0030] (6) using waste acid to adjust the pH value of liquid phase A to 8.5-10 for precipitation reaction, and then performing solid-liquid separation to obtain silicon-containing precipitate and liquid phase B;
[0031] (7) washing the silicon-containing precipitate and then roasting it to obtain a silicon product;
[0032] (8) Extracting the liquid phase B to obtain an extract; and then back-extracting the extract to obtain a vanadium-tungsten solution.
[0033] According to some embodiments of the present invention, there is no particular limitation on the source of the waste denitration catalyst, and any waste denitration catalyst produced by any process can be used, preferably a waste denitration catalyst with a damaged structure obtained by disassembling the waste denitration catalyst. The waste denitration catalyst mainly contains active ingredients such as titanium dioxide, tungsten trioxide and vanadium pentoxide. The selection range of the waste denitration catalyst is very wide. Preferably, the waste denitration catalyst is selected from at least one of a corrugated waste denitration catalyst, a plate-type waste denitration catalyst and a honeycomb waste denitration catalyst.
[0034] Al2O3 and SiO2 in the waste denitrification catalyst are a type of impurity that is difficult to remove in the TiO2 carrier recovery process. They are either coated by TiO2 stacking or condensed in the pores on the surface of the waste denitrification catalyst due to sintering, forming a strong physical bond with TiO2, resulting in dissolution through the recovery process reaction. The excessive content of Fe2O3 in the TiO2 product recovered from the waste denitrification catalyst is the main factor restricting its commercial value. The Fe2O3 component in the TiO2 product mainly comes from the fly ash deposited on the surface of the waste denitrification catalyst and the iron filings in the crushing process of the recovery process. The Fe2O3 component brought by the fly ash can be removed in large quantities through the surface cleaning process of the waste denitrification catalyst, while the iron filings generated in the grinding process are rarely paid attention to, which ultimately leads to these iron filings being dissolved by acidic solutions in the subsequent refining and modification process, and finally converted into Fe2O3 impurities. The inventors of the present invention have discovered in their research that, in the process of recovering waste denitrification catalysts, by grinding the waste denitrification catalysts to a particle size D90 of less than 800 nm, the physical bond between Al2O3, SiO2 and TiO2 can be broken, and physical depolymerization can be achieved, which is beneficial to making the first hot alkali reaction more complete and the impurity cleaning more thorough; at the same time, combined with the magnetic separation and iron removal process, the iron filings contained in the titanium slag can be removed, which can effectively reduce the content of Al2O3, SiO2 and Fe2O3 in the titanium tungsten powder.
[0035] According to some embodiments of the present invention, in order to further reduce the content of Al2O3 and SiO2 in the titanium-tungsten powder, preferably, in step (1), the particle size D90 of the crushed material is less than 500 nm.
[0036] According to some embodiments of the present invention, preferably, in step (1), the pretreatment step includes: deashing, washing and drying the spent denitration catalyst.
[0037] According to a preferred embodiment of the present invention, the pretreatment comprises the following steps:
[0038] a) Ash removal and cleaning: remove the ash on the surface and inside the pores of the spent denitration catalyst, collect the fly ash, and perform a first cleaning with water;
[0039] b) mixing the product obtained in step a) with a cleaning solution to perform a second cleaning;
[0040] c) drying the product obtained in step b) at 80-150° C. for 3-6 hours until the water content in the product is less than 5% by mass.
[0041] According to some embodiments of the present invention, preferably, in step a), the ash on the surface and inside the pores of the spent denitrification catalyst is thoroughly removed by negative pressure dust collection equipment and a blast dust collection chamber, the fly ash is collected, and then the catalyst pores are flushed with a high-pressure water gun to further remove the ash.
[0042] According to some embodiments of the present invention, preferably, in step b), the second cleaning is performed in an ultrasonic bubbling cleaning device to remove toxic substances in the micropores of the spent denitration catalyst. Further, in the second cleaning, the ultrasonic frequency is 28-40kHz, the power is 30-50W / L, the pressure of the bubbling compressed gas is 0.2-0.4MPa, and the bubbling time is 10-20min.
[0043] According to some embodiments of the present invention, preferably, in step b), the cleaning solution is selected from an acidic solution and / or an alkaline solution. Specifically, the acidic solution is selected from at least one of sulfuric acid, ammonium sulfate and nitric acid solutions with a molar concentration of 0.05-0.5 mol / L; the alkaline solution is selected from at least one of ammonia water, monoethanolammonium and urea solutions with a molar concentration of 0.05-0.5 mol / L.
[0044] According to some embodiments of the present invention, in step c), there is no particular limitation on the drying conditions, as long as the water content of the spent denitration catalyst after drying is less than 5% by mass. In the present invention, the water content of the spent denitration catalyst after drying is determined by weighing method.
[0045] According to some embodiments of the present invention, the drying can be performed in a conventional drying device in the art, for example, the drying can be performed in a forced air drying oven.
[0046] According to some embodiments of the present invention, in step (1), the grinding and crushing can be carried out in a conventional grinding equipment in the art, as long as a crushed material with a particle size D90 of less than 800 nm can be obtained. For example, the grinding and crushing can be carried out in a Raymond crusher. Preferably, the grinding and crushing can be specifically as follows: firstly the pretreated waste denitration catalyst is crushed in a Raymond crusher, and then ultrafine ground using a ball mill until the particle size D90 of the crushed material is less than 800 nm.
[0047] According to some embodiments of the present invention, in step (2), the alkali in the alkaline solution is selected from at least one of sodium hydroxide, potassium hydroxide and sodium carbonate.
[0048] According to some embodiments of the present invention, preferably, the mass concentration of the alkaline solution is 15-30%.
[0049] According to some embodiments of the present invention, preferably, the liquid-to-solid ratio of the alkaline solution to the pulverized material is 1-3:1 mL / g. When the liquid-to-solid ratio of the alkaline solution to the pulverized material meets the above range, the content of Al2O3 and SiO2 in the titanium-tungsten powder can be further reduced, and impurities such as As, P, and Hg in the pulverized material can also be removed.
[0050] According to some embodiments of the present invention, preferably, the conditions of the first thermal alkali reaction include: temperature of 100-180° C. and time of 30-120 min. When the first thermal alkali reaction is carried out under the above conditions, the contents of Al2O3 and SiO2 in the titanium tungsten powder can be further reduced.
[0051] According to some embodiments of the present invention, in step (3), the first high-titanium slag is subjected to iron removal to obtain a second high-titanium slag. The present invention does not particularly limit the method of iron removal, and can be carried out with reference to the prior art, as long as the iron-containing substances in the first high-titanium slag can be removed. In order to further reduce the content of Fe2O3 in titanium-tungsten powder, preferably, the iron removal process includes: mixing water and the first high-titanium slag in a liquid-solid ratio of 2-5:1 mL / g and then performing magnetic separation to obtain a second high-titanium slag.
[0052] In order to further reduce the content of Fe2O3 in the titanium-tungsten powder, preferably, the conditions of the magnetic separation include: the magnetic field induction intensity is 1.8-2.2T, and the number of magnetic separations is 3-5 times. The magnetic separation can be carried out in a conventional magnetic separation device in the art, as long as the iron-containing substances in the first high-titanium slag can be removed. For example, the magnetic separation can be intermittently operated using a real-time magnetic separation device (such as a fine powder wet magnetic separator) to physically remove iron from the first high-titanium slag.
[0053] According to some embodiments of the present invention, preferably, in step (4), the second high-titanium slag is mixed with a pickling solution for pickling; preferably, the amount of the pickling solution is such that the pH value of the mixture of the second high-titanium slag and the pickling solution is 1-4.
[0054] According to some embodiments of the present invention, preferably, the acid in the pickling solution is selected from sulfuric acid and / or hydrochloric acid.
[0055] According to some embodiments of the present invention, preferably, the mass concentration of the pickling solution is 5-15%.
[0056] According to some embodiments of the present invention, preferably, the liquid-to-solid ratio of the pickling solution to the second high-titanium slag is 1-2:1 mL / g. When the liquid-to-solid ratio of the pickling solution to the second high-titanium slag meets the above requirements, harmful impurities such as alkali metals remaining in the second high-titanium slag can be effectively removed.
[0057] According to some embodiments of the present invention, preferably, the pickling conditions include: a temperature of 70-90° C. and a time of 45-90 min.
[0058] According to some embodiments of the present invention, preferably, step (4) further comprises the step of washing and drying the solid obtained after solid-liquid separation. Preferably, the washing is performed so that the solid is washed with water until the conductivity of the solution produced by washing is less than 400 μS / cm. More preferably, the solid is pulped and washed, specifically: the solid is mixed with water to obtain a mixed solution, and the amount of water added is such that the mass ratio of the solid to water is 1:1. The number of pulping and washing is preferably 4-7 times.
[0059] According to some embodiments of the present invention, preferably, the drying conditions include: a temperature of 100-250° C., preferably 120-150° C.; and a time of 90-180 min, preferably 90-120 min.
[0060] According to some embodiments of the present invention, the conductivity is measured using a potentiometric-pH meter method.
[0061] According to some embodiments of the present invention, after the pickling and washing in step (4), harmful impurities such as alkali metals in the second high-titanium slag can be further removed, and the contents of Al2O3, SiO2 and Fe2O3 in the titanium-tungsten powder can be reduced.
[0062] According to some embodiments of the present invention, preferably, in step (4), based on the total amount of the titanium-tungsten powder, the content of Na2O in the titanium-tungsten powder is 0.01-0.02 mass %, the content of Al2O3 is 0.05-0.095 mass %, the content of SiO2 is 1.7-1.95 mass %, the content of TiO2 is 90-93 weight %, the content of WO3 is 2.85-3.15 mass %, the content of Fe2O3 is 0.01-0.03 mass %, and the content of SO3 is 2.15-3.45 mass %.
[0063] According to some embodiments of the present invention, preferably, the titanium tungsten powder further contains V2O5; more preferably, based on the total amount of the titanium tungsten powder, the content of V2O5 in the titanium tungsten powder is 0.1-0.2% by mass. The titanium tungsten powder prepared by the method of the present invention is similar in composition to commercial titanium tungsten powder, and its composition and content are basically close to those of commercial titanium tungsten powder, and can be used as a carrier raw material for the production of denitration catalysts.
[0064] According to some embodiments of the present invention, preferably, in step (5), the concentration of sodium in the waste alkali solution is 70000-83200 mg / L, the concentration of silicon is 3800-4900 mg / L, the concentration of vanadium is 200-300 mg / L, the concentration of tungsten is 2500-3150 mg / L, and the concentration of aluminum is 80-150 mg / L. + , silicon, vanadium, tungsten and aluminum exist in the form of acid radicals.
[0065] According to some embodiments of the present invention, preferably, the concentration of hydroxide ions in the waste alkali solution is 4-5 mol / L.
[0066] According to some embodiments of the present invention, in step (5), the waste alkali liquid is mixed with fly ash to carry out a second hot alkali reaction. Since the waste alkali liquid contains substances such as V, W, Na, Si, Al, etc., during the hydrothermal reaction with the fly ash, multiple components couple and flocculated colloids are formed. The pH value of the waste alkali liquid drops to below 12.5 at the reaction temperature, reaching the precipitation range of HAlO2, thereby increasing the aluminum-silicon ratio of the desiliconized fly ash.
[0067] According to some embodiments of the present invention, the fly ash may be conventional fly ash in the art, preferably ash from the surface and pores of the waste denitration catalyst collected during the pretreatment of the waste denitration catalyst. More preferably, based on the total amount of the fly ash, the fly ash has a Na2O content of 0.13-0.15% by mass, an Al2O3 content of 35-40% by mass, a SiO2 content of 34-39% by mass, and a TiO2 content of 1.5-2% by mass.
[0068] According to some embodiments of the present invention, preferably, the liquid-solid ratio of the waste alkali solution to fly ash is 2-7.5:1 mL / g; when the liquid-solid ratio of the waste alkali solution to fly ash meets the above requirements, the aluminum-silicon ratio of the desiliconized fly ash can be further improved.
[0069] According to some embodiments of the present invention, preferably, the conditions of the second thermal alkali reaction include: pH value of 11-12.5, temperature of 90-170° C., and time of 40-120 min.
[0070] According to some embodiments of the present invention, preferably, based on the total amount of the desiliconized fly ash, the content of Al2O3 in the desiliconized fly ash is 41-48% by mass, the content of SiO2 is 25-33% by mass, and the content of TiO2 is 1.5-2% by mass;
[0071] According to some embodiments of the present invention, preferably, the desiliconized fly ash further contains Na2O; more preferably, based on the total amount of the desiliconized fly ash, the content of Na2O in the desiliconized fly ash is 3-9% by mass.
[0072] According to some embodiments of the present invention, preferably, the aluminum-silicon ratio of the desiliconized fly ash is 1.2-1.8:1.
[0073] According to some embodiments of the present invention, preferably, the XRD spectrum of the desiliconized fly ash does not have a characteristic peak of amorphous SiO2 within the range of 2θ=15°-40°. The characteristic peak of amorphous SiO2 refers to a gentle curve peak type within the range of 2θ=15°-40°, called a "mantou peak". The XRD spectrum of the desiliconized fly ash does not have a characteristic peak of amorphous SiO2 within the range of 2θ=15°-40°, that is, there is no characteristic peak in the form of a "mantou peak" representing amorphous SiO2 within the range of 2θ=15°-40° in the XRD spectrum. The method can dissolve amorphous SiO2 in fly ash by using waste alkali liquid, and compared with pure alkali liquid, the waste alkali liquid used in the method has better silicon dissolving ability.
[0074] According to some embodiments of the present invention, preferably, in step (6), the waste acid solution contains about 13-18% by mass of H + , and a small amount of titanic acid. For liquid phase A, the elements contained in the waste acid liquid will not affect the precipitation reaction of obtaining silicon-containing precipitates and the purity of silicon products. It is not only suitable as a pH regulator, but also can realize the utilization of waste liquid, which is beneficial to reducing costs and protecting the environment.
[0075] According to some embodiments of the present invention, in step (6), waste acid is used to adjust the pH value of liquid phase A, the ambient temperature is controlled between 20-80°C, and the pH value of liquid phase A is adjusted to 8.5-10, thereby allowing the silicon-containing precipitate to precipitate.
[0076] According to some embodiments of the present invention, in order to further improve the silicon extraction rate and the purity of the silicon product, preferably, the conditions of the precipitation reaction include: a temperature of 20-80° C. and a time of 45-90 min.
[0077] In the present invention, there is no particular limitation on the solid-liquid separation method in steps (2), (4), (5) and (6), which can be conventionally selected in the art, and can be selected by those skilled in the art according to actual conditions. The method further comprises the step of washing the solid obtained after the solid-liquid separation, for example, the solid can be washed with water, and the present invention does not particularly limit the number of washing times, for example, the number of washing times can be 1-7 times.
[0078] According to some embodiments of the present invention, the silicon-containing precipitate can be used as a raw material to be made into molecular sieves, nano-SiO2 microspheres, refractory materials, quartz building materials, etc. through refining, purification, roasting, recrystallization, etc.
[0079] According to some embodiments of the present invention, preferably, the pH value of the liquid phase B is 7.3-9.5.
[0080] According to some embodiments of the present invention, in step (7), the silicon-containing precipitate is washed and then calcined to obtain a silicon product.
[0081] According to some embodiments of the present invention, preferably, in step (7), the calcination conditions include: a temperature of 350-450° C. and a time of 60-120 min.
[0082] According to some embodiments of the present invention, preferably, in step (7), based on the total amount of the silicon product, the content of SiO2 in the silicon product is 94% by mass or more, preferably 94-97% by mass.
[0083] According to some embodiments of the present invention, preferably, in step (8), a composite extractant is used to extract liquid phase B, and when the pH value of liquid phase B is within the above-mentioned specific pH value range (7.3-9.5), vanadium and tungsten are extracted into the organic phase through anion association reaction, while cations such as potassium and sodium remain in the aqueous phase, thereby achieving further purification of vanadium and tungsten on the one hand and enrichment of the vanadium and tungsten solution on the other hand.
[0084] Preferably, the composite extractant is an acidified composite extractant. Specifically, the composite extractant is mixed with 15 mass % sulfuric acid in a volume ratio of 1:1 to obtain the acidified composite extractant.
[0085] According to some embodiments of the present invention, preferably, in step (8), the composite extractant comprises a main extractant, a co-extractant, a phase regulator and a diluent;
[0086] According to some embodiments of the present invention, preferably, based on the total amount of the composite extractant, the content of the main extractant in the composite extractant is 10-50% by mass, the content of the synergistic extractant is 5-18% by mass, the content of the phase regulator is 2.5-10% by mass, and the content of the diluent is 40-70% by mass.
[0087] According to some embodiments of the present invention, preferably, in the composite extractant, the mass ratio of the main extractant, the co-extractant, the phase regulator and the diluent is 4-6:1-5:1-3:2-4.
[0088] According to some embodiments of the present invention, preferably, the main extractant is selected from at least one of a primary amine salt, a secondary amine salt, a tertiary amine salt and a quaternary ammonium salt, preferably a tertiary amine salt.
[0089] When the amine salt comes into contact with liquid phase B, an exchange reaction occurs with the tungsten isopolyacid anions in the solution:
[0090]
[0091]
[0092]
[0093] When the amine salt comes into contact with liquid phase B, an exchange reaction occurs with the vanadium isopolyacid anions in the solution:
[0094]
[0095]
[0096]
[0097]
[0098] Through extraction, the selective extraction of polymerized anions vanadate and tungstate can be achieved, while cations such as potassium and sodium or non-polymerized anions such as sulfate in the solution are not extracted, so the purification and enrichment of vanadium and tungsten can be achieved.
[0099] According to some embodiments of the present invention, preferably, the synergist is selected from at least one of tetrakis-(diethylamino)phosphonium bromide (TPB), lipid tributyl phosphate and trialkylphosphonium oxide, preferably tetrakis-(diethylamino)phosphonium bromide.
[0100] According to some embodiments of the present invention, preferably, the phase regulator is selected from at least one of higher alcohols, secondary octanol and n-butanol, preferably secondary octanol.
[0101] According to some embodiments of the present invention, preferably, the diluent is sulfonated kerosene.
[0102] According to some embodiments of the present invention, preferably, the oil-to-liquid ratio of liquid phase B to the composite extractant is 2-5:1.
[0103] According to some embodiments of the present invention, preferably, in step (8), the extract is stripped with ammonia water. Stripping the extract obtained by extraction with ammonia water can strip vanadium and tungsten into the aqueous phase to form ammonium vanadate and ammonium tungstate, and the organic phase is acidified and then used continuously, thereby increasing the concentration of vanadium and tungsten in the vanadium-tungsten solution and significantly reducing the cost.
[0104] The reactions that occur during the stripping process are as follows:
[0105] (R3NH)4H2W 12 O 39(org) +24NH4OH (aq) →R3N (org) +12(NH4)2WO 4(aq) +15H2O
[0106] (R3NH)4H2V10 O 28(org) +10NH4OH (aq) →4R3N (org) +10(NH4)VO 3(aq) +8H2O.
[0107] According to some embodiments of the present invention, preferably, the mass concentration of the ammonia water is 7.5-15%.
[0108] According to some embodiments of the present invention, preferably, the ratio of aqueous ammonia to the oil-liquid of the extract is 1-3:1.
[0109] According to some embodiments of the present invention, the silicon extraction rate of the method is above 90%, preferably above 92%, and more preferably 92-95%.
[0110] The method of the present invention adopts a specific composite extractant to extract vanadium and tungsten under alkaline conditions, and can achieve a high extraction efficiency. Preferably, the vanadium extraction rate of the method is above 99%, more preferably 99.12-99.36%; preferably, the tungsten extraction rate of the method is above 98%, more preferably 98.46-98.7%.
[0111] The method of the present invention can achieve a silicon extraction rate of more than 90% and a silicon product purity of more than 94% at normal temperature and pressure, can meet the raw material requirements of the foundry industry above IV level, and can also effectively recycle resources such as vanadium, tungsten, titanium, etc. in the waste denitration catalyst. The fly ash associated with the waste denitration catalyst is treated by the waste acid and waste alkali generated in the process of recovering the waste denitration catalyst, and the fly ash can be reduced while reducing the waste liquid. On the basis of ensuring the recovery quality of high value-added products, the amount of waste liquid and waste residue in the process of recovering the waste denitration catalyst is reduced, and the environmental protection cost of the waste denitration catalyst recovery is reduced, so as to achieve the purpose of treating waste with waste, which is beneficial to reducing costs and protecting the environment.
[0112] The present invention will be described in detail below by way of examples. In the following examples and comparative examples:
[0113] Solid index test: Test the composition of titanium tungsten powder by XRF.
[0114] Liquid index test: ICP is used to test the composition of waste alkali solution, liquid phase A and vanadium tungsten solution.
[0115] Silicon extraction rate test: The volumes of the waste alkali solution and liquid phase B in the embodiment and the comparative example were measured using a measuring cylinder, the concentration of SiO2 in the waste alkali solution and liquid phase B in the embodiment and the comparative example was detected by ICP, and the silicon extraction rate η was calculated by the total amount method:
[0116]
[0117] Where: V1—volume of waste alkali solution, mL;
[0118] C1—concentration of SiO2 in waste alkali solution, mg / L;
[0119] V2—volume of liquid phase B, mL;
[0120] C2—Concentration of SiO2 in liquid phase B, mg / L.
[0121] Purity test of silicon products: XRF is used to detect the mass proportion of SiO2 in silicon products.
[0122] The calculation formula for the extraction rate test is as follows:
[0123]
[0124] Where: η′—extraction rate, %;
[0125] C a —Concentration of the element in the liquid phase before extraction, mg / L, obtained by ICP analysis;
[0126] V a —The volume of the liquid phase before extraction, mL;
[0127] C b —Concentration of elements in the liquid phase after extraction, mg / L, obtained by ICP analysis;
[0128] V b —Volume of the liquid phase after extraction, mL.
[0129] The spent denitrification catalyst comes from a power plant of the State Energy Group. Its main components are:
[0130] V2O5: 0.6-1.8% by mass, TiO2: 85-89% by mass,
[0131] WO3: 4.5-5.5 mass%, SiO2: 3.5-5.5 mass%.
[0132] N263: tertiary amine extractant, commercially available;
[0133] TPB: tetrakis-(diethylamino)phosphonium bromide, commercially available;
[0134] Other raw materials used in the examples and comparative examples are all commercially available.
[0135] Example 1
[0136] (1) Selecting a honeycomb waste denitration catalyst, using a negative pressure dust suction device and a blast dust collection chamber to remove dust from the catalyst surface and the inside of the pores for 5 minutes, collecting fly ash, and then flushing the catalyst pores with a high-pressure water gun for 5 minutes; then placing the denitration waste denitration catalyst after ash removal in an ultrasonic bubbling cleaning device filled with a sulfuric acid solution (concentration of 0.25 mol / L) for cleaning, the ultrasonic frequency is 28 kHz, the power is 40 W / L, the pressure of the bubbling compressed air is 0.2 MPa, and the bubbling time is 10 minutes; finally, the cleaned waste denitration catalyst is dried at 120° C., so that the water content of the waste denitration catalyst after drying is 5% by mass;
[0137] The deashed, cleaned and dried spent denitration catalyst is disassembled, then crushed in a Raymond crusher, and ground to a particle size of D90≤800nm to obtain a crushed material;
[0138] (2) According to the alkaline solution / crushed material (liquid-to-solid ratio) of 1.5:1 mL / g, 500 g of crushed material was mixed with 750 mL of alkaline solution (20 mass%), and the mixture was reacted at 140° C. for 120 min. After the reaction, the mixed solution was cooled to room temperature, and the mixed solution was separated from the solid by a filter press to obtain a first solid phase and a first liquid phase; the first solid phase was washed once with 500 mL of water, and then separated from the solid by a liquid to obtain a first high-titanium slag and a second liquid phase; the first liquid phase and the second liquid phase were mixed to obtain a waste alkaline solution;
[0139] (3) mixing water and the first high-titanium slag in a liquid-solid ratio of 2:1 mL / g, and then using a fine powder wet magnetic separator to perform magnetic separation and iron removal at a magnetic field induction intensity of 2.2 T, the number of magnetic separations is 3 times, and a second high-titanium slag is obtained;
[0140] (4) According to the acid solution / second high titanium slag (liquid-solid ratio) of 1:1 mL / g, 500 g of the second high titanium slag was mixed with 500 mL of sulfuric acid solution (15 mass%) and poured into a reactor to an initial pH value of 1.2. After stirring and reacting at 85°C for 90 minutes, filter pressing and solid-liquid separation were performed to obtain a second solid phase and waste acid liquid; the second solid phase was washed with clean water for 3 times until the conductivity was less than 365 μs / cm, and the obtained solid was dried at 150°C for 90 minutes to obtain titanium tungsten powder;
[0141] (5) 20 g of the fly ash collected in step (1) was mixed with 80 mL of waste alkali solution (OH) at a liquid-solid ratio of 4:1 mL / g. -The mixture was reacted at 90°C for 120 minutes, and the mixture was cooled to room temperature. The mixture was separated into solid and liquid by a filter press to obtain a third solid phase and a liquid phase A. The third solid phase was washed with water for 3 times until the conductivity was less than 365 μS / cm, and the obtained solid was dried at 150°C for 90 minutes to obtain desiliconized fly ash.
[0142] (6) at 50° C., using the waste acid solution in step (4) to adjust the pH value of liquid phase A to 9.5, performing a precipitation reaction, and then performing solid-liquid separation to obtain a silicon-containing precipitate and liquid phase B;
[0143] (7) washing the silicon-containing precipitate with clean water for three times until the conductivity is less than 365 μS / cm, and then calcining the obtained solid at 450° C. for 120 min to obtain a silicon product;
[0144] (8) After adding sulfuric acid solution (10% by mass) to liquid phase B to adjust the pH value of liquid phase B to 9.5, liquid phase B is centrifuged and extracted with an acidified composite extractant at an O / A ratio of 2:1 to obtain an extract; wherein, in the composite extractant, N263:TPB:octanol:sulfonated kerosene = 45:10:10:35 (mass ratio); the extract is back-extracted with 10% by mass ammonia water at an O / A ratio of 2:1 to obtain a vanadium tungsten solution.
[0145] Example 2
[0146] The process is carried out in a manner similar to that of Example 1, except that in step (1), the particle size D90 of the crushed material is ≤500 nm; in step (5), the liquid-to-solid ratio of the waste alkali liquid to the fly ash is 2:1 mL / g; and in step (6), at 50°C, the pH value of the liquid phase A is adjusted to 8.5 using the waste acid liquid in step (4).
[0147] Example 3
[0148] The process is carried out in a manner similar to that of Example 1, except that in step (1), the particle size D90 of the crushed material is ≤650 nm; in step (5), the liquid-to-solid ratio of the waste alkali liquid to the fly ash is 7.5:1 mL / g; and in step (6), at 50°C, the pH value of the liquid phase A is adjusted to 10 using the waste acid liquid in step (4).
[0149] Comparative Example 1
[0150] Titanium tungsten powder is prepared according to steps (1) to (4) of Example 1, except that step (3) of removing iron from the first high-titanium slag is not performed in step (1) to obtain titanium tungsten powder.
[0151] Comparative Example 2
[0152] The process is carried out in a similar manner to Example 1, except that the waste alkali solution in step (5) is replaced by a 4.65 mol / L NaOH solution; the waste acid solution in step (6) is replaced by a H2SO4 solution (mass fraction is 13%); and the composite extractant in step (8) is N263: sulfonated kerosene = 45:55 (mass ratio).
[0153] The titanium tungsten powders obtained in Examples 1-3 and Comparative Example 1 were subjected to XRF analysis, and the results are shown in Table 1:
[0154] Table 1
[0155]
[0156]
[0157] Note: Content* is the mass percentage
[0158] From the results in Table 1, it can be seen that the titanium tungsten powder prepared by the method of the present invention is similar to the commercial titanium tungsten powder in composition, and its composition and content are basically close to those of the commercial titanium tungsten powder, and can be used as a carrier raw material for the production of denitration catalysts. By comparing the composition and content of the titanium tungsten powder prepared in Example 1 with that in Comparative Example 1, it can be seen that the method of the present invention can effectively reduce the content of Al2O3, SiO2 and Fe2O3 in the titanium tungsten powder.
[0159] The waste alkali liquor and liquid phase A of Examples 1-3 and Comparative Example 2 were subjected to ICP analysis and pH test. The results are shown in Table 2:
[0160] Table 2
[0161]
[0162] The fly ash and desiliconized fly ash of Examples 1-3 and Comparative Example 2 were subjected to XRF analysis, and the results are shown in Table 3:
[0163] Table 3
[0164]
[0165]
[0166] Note: Content* is the mass percentage
[0167] It can be seen from the results of Table 2 and Table 3 that in the method of the present invention, the waste alkali liquid contains substances such as V, W, Na, Si, Al, etc. During the hydrothermal reaction with fly ash, due to the coupling of multiple components and the formation of flocculent colloids, compared with the NaOH solution with the same alkali concentration used in Comparative Example 2, the pH value of the waste alkali liquid in the method of the present invention drops to below 12.5 at the reaction temperature, reaching the precipitation range of HAlO2, thereby improving the aluminum-silicon ratio of the desiliconized fly ash; by comparing the content of SiO2 in fly ash, the desiliconized fly ash of the present invention, and the desiliconized fly ash of Comparative Example 2, it can be seen that the waste alkali liquid used in the method of the present invention has a good silicon dissolving ability.
[0168] The fly ash and desiliconized fly ash of Examples 1-3 and Comparative Example 2 were subjected to XRD analysis. The present invention exemplarily provides XRD spectra of the fly ash and the desiliconized fly ash of Example 1 and the desiliconized fly ash of Comparative Example 2, as shown in FIG. Figure 1 As shown in the figure, it can be seen that compared with the XRD spectra of fly ash and desiliconized fly ash of comparative example 2, in the XRD spectrum of desiliconized fly ash of the present invention, the characteristic peak ("mantou peak") representing amorphous SiO2 in the range of 2θ=15°-40° basically disappears, indicating that the method of the present invention can dissolve amorphous SiO2 in fly ash by using waste alkali solution.
[0169] The fly ash mass reduction Δm, silicon extraction rate η and silicon product purity φ of Examples 1-3 and Comparative Example 2 were calculated. The results are shown in Table 4:
[0170] Table 4
[0171]
[0172]
[0173] Note: The fly ash mass reduction Δm is the difference between the mass of fly ash and the mass of desiliconized fly ash.
[0174] It can be seen from the results in Table 4 that the mass changes of fly ash before and after the reaction are similar, indicating that the method of the present invention can also achieve the silicon extraction effect for fly ash by using waste alkali solution, and the silicon extraction effect of the present invention is very close to that of Comparative Example 2. The use of waste acid and waste alkali to treat fly ash can achieve a silicon extraction rate of more than 90% and a silicon product purity of more than 94%, achieving the purpose of treating waste with waste, which is beneficial to reducing costs and making greater contributions from an environmental protection perspective.
[0175] The liquid phase B and the vanadium-tungsten solution of Examples 1-3 and Comparative Example 2 were subjected to ICP analysis, and then the vanadium extraction rate and the tungsten extraction rate of Examples 1-3 and Comparative Example 2 were calculated. The results are shown in Table 5:
[0176] Table 5
[0177] project Total V (mg) WTotal amount (mg) V extraction rate (%) W extraction rate (%) Liquid phase B 20.4 32.41 - - Example 1 Vanadium-tungsten solution 0.15 0.4342 99.26 98.46 Example 2 Vanadium Tungsten Solution 0.18 0.4219 99.12 98.70 Example 3 Vanadium Tungsten Solution 0.13 0.4381 99.36 98.65 Comparative Example 2 Vanadium Tungsten Solution 0.74 14.78 96.37 56.39
[0178] It can be seen from the results in Table 5 that the method of the present invention uses a specific composite extractant to extract V and W under alkaline conditions, and can achieve an extraction efficiency of more than 98%.
[0179] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for treating spent denitration catalyst and fly ash, characterized in that: The method comprises the following steps: (1) Pre-treating the spent denitration catalyst, and then grinding, crushing, and screening to obtain a crushed material, wherein the particle size D90 of the crushed material is less than 800 nm; (2) mixing the crushed material with an alkaline solution to perform a first thermal alkali reaction, and then performing solid-liquid separation to obtain a first high-titanium slag and a waste alkali solution; (3) removing iron from the first high-titanium slag to obtain a second high-titanium slag; (4) pickling the second high-titanium slag and then performing solid-liquid separation to obtain titanium-tungsten powder and waste acid liquid; (5) mixing the waste alkali liquid with fly ash to carry out a second hot alkali reaction, and then performing solid-liquid separation to obtain desiliconized fly ash and liquid phase A; (6) using waste acid to adjust the pH value of liquid phase A to 8.5-10 for precipitation reaction, and then performing solid-liquid separation to obtain silicon-containing precipitate and liquid phase B; (7) washing the silicon-containing precipitate and then roasting it to obtain a silicon product; (8) extracting the liquid phase B to obtain an extract; The extract is then stripped to obtain a vanadium-tungsten solution.
2. The method according to claim 1, wherein: In step (1), the particle size D90 of the crushed material is less than 500 nm.
3. The method according to claim 1, wherein: In step (1), the pretreatment step includes: deashing, washing and drying the spent denitration catalyst.
4. The method according to any one of claims 1 to 3, wherein: In step (2), the alkali in the alkaline solution is selected from at least one of sodium hydroxide, potassium hydroxide and sodium carbonate.
5. The method according to any one of claims 1 to 3, wherein: In step (2), the mass concentration of the alkaline solution is 15-30%.
6. The method according to any one of claims 1 to 3, wherein: In step (2), the liquid-to-solid ratio of the alkaline solution to the crushed material is 1-3:1 mL / g.
7. The method according to any one of claims 1 to 3, wherein: In step (2), the conditions of the first thermal alkali reaction include: temperature of 100-180° C. and time of 30-120 min.
8. The method according to any one of claims 1 to 3, wherein: In step (3), the iron removal process includes: mixing water and the first high-titanium slag evenly according to a liquid-solid ratio of 2-5:1 mL / g, and then performing magnetic separation to obtain a second high-titanium slag.
9. The method according to claim 8, wherein: The conditions for magnetic separation include: the magnetic field induction intensity is 1.8-2.2T, and the number of magnetic separations is 3-5 times.
10. The method according to any one of claims 1 to 3, wherein: In step (4), the second high-titanium slag is mixed with a pickling solution for pickling.
11. The method according to claim 10, wherein: The amount of the pickling solution is such that the pH value of the mixture of the second high-titanium slag and the pickling solution is 1-4.
12. The method according to claim 10, wherein: The acid in the pickling solution is selected from sulfuric acid and / or hydrochloric acid; the mass concentration of the pickling solution is 5-15%.
13. The method according to claim 10, wherein: The liquid-to-solid ratio of the pickling solution to the second high-titanium slag is 1-2:1 mL / g.
14. The method according to claim 10, wherein: The pickling conditions include: a temperature of 70-90° C. and a time of 45-90 min.
15. The method according to any one of claims 1 to 3, wherein: In step (4), based on the total amount of the titanium tungsten powder, the content of Na2O in the titanium tungsten powder is 0.01-0.02% by mass, the content of Al2O3 is 0.05-0.095% by mass, the content of SiO2 is 1.7-1.95% by mass, the content of TiO2 is 90-93% by weight, the content of WO3 is 2.85-3.15% by mass, the content of Fe2O3 is 0.01-0.03% by mass, and the content of SO3 is 2.15-3.45% by mass.
16. The method according to claim 15, wherein: The titanium-tungsten powder also contains V2O5.
17. The method according to claim 16, wherein: Based on the total amount of the titanium-tungsten powder, the content of V2O5 in the titanium-tungsten powder is 0.1-0.2 mass %.
18. The method according to any one of claims 1 to 3, wherein: In step (5), the concentration of sodium in the waste alkali solution is 70000-83200 mg / L, the concentration of silicon is 3800-4900 mg / L, the concentration of vanadium is 200-300 mg / L, the concentration of tungsten is 2500-3150 mg / L, and the concentration of aluminum is 80-150 mg / L, calculated on the basis of elements.
19. The method according to any one of claims 1 to 3, wherein: In step (5), the concentration of hydroxide ions in the waste alkali solution is 4-5 mol / L.
20. The method according to any one of claims 1 to 3, wherein: Based on the total amount of the fly ash, the content of Na2O in the fly ash is 0.13-0.15% by mass, the content of Al2O3 is 35-40% by mass, the content of SiO2 is 34-39% by mass, and the content of TiO2 is 1.5-2% by mass.
21. The method according to any one of claims 1 to 3, wherein: The liquid-to-solid ratio of the waste alkali liquid to fly ash is 2-7.5:1 mL / g.
22. The method according to any one of claims 1 to 3, wherein: The conditions of the second thermal alkali reaction include: pH value of 11-12.5, temperature of 90-170° C., and time of 40-120 min.
23. The method according to any one of claims 1 to 3, wherein: Based on the total amount of the desiliconized fly ash, the content of Al2O3 in the desiliconized fly ash is 41-48% by mass, the content of SiO2 is 25-33% by mass, and the content of TiO2 is 1.5-2% by mass.
24. The method according to claim 23, wherein: The aluminum-silicon ratio of the desiliconized fly ash is 1.2-1.8:
1.
25. The method according to any one of claims 1 to 3, wherein: In step (6), the conditions of the precipitation reaction include: temperature of 20-80° C. and time of 45-90 min.
26. The method according to any one of claims 1 to 3, wherein: The pH value of the liquid phase B is 7.3-9.
5.
27. The method according to any one of claims 1 to 3, wherein: In step (7), the calcination conditions include: temperature of 350-450° C. and time of 60-120 min.
28. The method according to any one of claims 1 to 3, wherein: In step (7), based on the total amount of the silicon product, the content of SiO2 in the silicon product is greater than 94% by mass.
29. The method according to claim 28, wherein: In step (7), based on the total amount of the silicon product, the content of SiO2 in the silicon product is 94-97% by mass.
30. The method according to any one of claims 1 to 3, wherein: In step (8), liquid phase B is extracted using a composite extractant.
31. The method according to claim 30, wherein: The composite extractant comprises a main extractant, a co-extractant, a phase regulator and a diluent.
32. The method according to claim 31, wherein: Based on the total amount of the composite extractant, the content of the main extractant in the composite extractant is 10-50% by mass, the content of the synergistic extractant is 5-18% by mass, the content of the phase regulator is 2.5-10% by mass, and the content of the diluent is 40-70% by mass.
33. The method according to claim 31 or 32, wherein: The main extractant is selected from at least one of primary amine salts, secondary amine salts, tertiary amine salts and quaternary ammonium salts.
34. The method according to claim 31 or 32, wherein: The synergistic extractant is selected from at least one of tetrakis-(diethylamino)phosphonium bromide, lipid tributyl phosphate and trialkylphosphonium oxide.
35. The method according to claim 31 or 32, wherein: The phase regulator is selected from at least one of higher alcohols, secondary octanol and n-butanol.
36. The method according to claim 31 or 32, wherein: The diluent is sulfonated kerosene.
37. The method of claim 30, wherein: In the composite extractant, the mass ratio of the main extractant, the co-extractant, the phase regulator and the diluent is 4-6:1-5:1-3:2-4.
38. The method of claim 30, wherein: The oil-to-liquid ratio of liquid phase B to the composite extractant is 2-5:
1.
39. The method according to any one of claims 1 to 3, wherein: In step (8), the extract is back-extracted using aqueous ammonia.
40. The method of claim 39, wherein: The mass concentration of the ammonia water is 7.5-15%.
41. The method of claim 39, wherein: The oil-liquid ratio of ammonia water to extract is 1-3:1.
Citation Information
Patent Citations
Method for fully recovering silicon dioxide in waste SCR (Selective Catalyst Reduction) catalyst
CN104261415A
Preparation method and application of desiliconized fly ash
CN108285163A
Collaborative fusion treatment method of abandoned SCR flue gas denitrification catalyst and fly ash
CN110548748A
Method for extraction of vanadium from waste SCR catalyst and preparation of activated titanium silicon tungsten powder
CN106521160A
Recycling method of waste SCR denitration catalyst
CN106866073A
